The contexts of learning, literacy practices and knowledge construction of University of the Philippines Visayas M.Ed. students - Bautista, Aurora Fe C. (Danyag :the UPV journal of humanities and social sciences)
"This study describes the contexts of learning, literacy practices and knowledge construction of the thirty four graduate students in the University of the Philippines Visayas M.Ed. program. Analysis of data derived from a series of interviews, a survey of study approaches, and examination of student's essays revealed commonalities and differences among two age groups. Study goals articulated by younger students included association with the prestige of the University of the Philippines and gaining job stability; for their older counterparts, opportunity for promotion in rank, and to gain personal fulfillment in being able to adapt to an ever changing world. Both groups of students faced difficuties in fulfilling graduate program standards, overcoming financial constraints and resolving conflicts between personal and academic goals and priorities. Literacy practices of younger students focused on building background knowledge from textual materials, and for their older counterparts, group discussions relating new theories and concepts to experience. Knowledge construction for younger students involved mostly reformulation and interpretation of textual materials, and for their older counterparts, the application new concepts and theories to real life situations. Both groups expressed insights about learning as changing one's perspectives, becoming a different person, and realizations about group sharing and interactions as mechanisms for deeper learning and understanding."